Civil Law Analysis of the Misuse of Legal Entities for Personal Interests (Piercing the Corporate Veil) in Indonesia - Judijanto, Loso; Triyantoro, Andri; Susilo, Anton (Eastasouth Institute, 2025)
This paper explores the concept of